Genus- and Species-Specific PCR-Based Detection of Dairy Propionibacteria in Environmental Samples by Using Primers Targeted to the Genes Encoding 16S rRNA - Rossi, Franca (American Society for Microbiology, 1999)
PCR assays with primers targeted to the genes encoding 16S rRNA were developed for detection of dairy propionibacteria. Propionibacterium thoenii specific oligonucleotide PT3 was selected after partial resequencing. Tests allowed the detection of less than 10 cells per reaction from milk and cheese and 10(2) cells per reaction from forage and soil.